VARIATION OF THE ETHANOL YIELD DURING VERY RAPID BATCH FERMENTATION OF SUGAR-CANE BLACKSTRAP MOLASSES - W. Borzani (Brazilian Journal of Chemical Engineering, 1998)
During rapid ethanol fermentation (2-3 h) of sugar-cane blackstrap molasses, a significant increase in the ethanol yield was frequently observed as fermentation proceeded, eventually leading to yields higher than the theoretical value when the end of the process was approached. In order to explain the above facts, three assumptions were examined: 1. temporary ethanol accumulation within the yeast cells; 2. variation of the dry matter content and/or of the microorganism density during the fermentation; 3. transformation of sugars into undetectable extra-cellular fermentable compounds at the initial stages of the process. Based on the experimental results presented here, the third of the above assumptions seems to explain the observed increase in the ethanol yield.